2004
DOI: 10.1074/jbc.c400124200
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Resonance Raman Detection of the Heme a3-Fe-CO and CuB-CO Species in CO-bound ba3-Cytochrome c Oxidase from Thermus thermophilus

Abstract: Understanding of the chemical nature of the dioxygen and nitric oxide moiety of ba 3 -cytochrome c oxidase from Thermus thermophilus is crucial for elucidation of its physiological function. In the present work, direct resonance Raman (RR) observation of the Fe-C-O stretching and bending modes and the C-O stretching mode of the Cu B -CO complex unambiguously establishes the vibrational characteristics of the heme-copper moiety in ba 3 -oxidase. We assigned the bands at 507 and 568 cm ؊1 to the Fe-CO stretching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 21 publications
4
39
0
Order By: Relevance
“…29 In our IR experiments, lines were detected at 1966, 1973, 1981, and 2053 cm −1 (Figure 2B, trace a), among which the line at 2053 cm −1 is assignable to the C–O stretching mode of the Cu B –CO species ( ν CuB C–O ), which is in a thermal equilibrium with the heme a 3 -CO species. 30,32 On the contrary, the frequencies of the former three bands are in very good agreement with the ν C–O of the heme a 3 -CO adduct reported by Varotsis and co-workers (1967, 1973, and 1982 cm −1 ). 29,30 However, the relative intensity among the three ν C–O bands, especially the ratio between the highest (1981–1982 cm −1 ) and lowest (1966–1967 cm −1 ) frequency bands was significantly different between our investigation and theirs.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…29 In our IR experiments, lines were detected at 1966, 1973, 1981, and 2053 cm −1 (Figure 2B, trace a), among which the line at 2053 cm −1 is assignable to the C–O stretching mode of the Cu B –CO species ( ν CuB C–O ), which is in a thermal equilibrium with the heme a 3 -CO species. 30,32 On the contrary, the frequencies of the former three bands are in very good agreement with the ν C–O of the heme a 3 -CO adduct reported by Varotsis and co-workers (1967, 1973, and 1982 cm −1 ). 29,30 However, the relative intensity among the three ν C–O bands, especially the ratio between the highest (1981–1982 cm −1 ) and lowest (1966–1967 cm −1 ) frequency bands was significantly different between our investigation and theirs.…”
Section: Resultssupporting
confidence: 89%
“…30,32 On the contrary, the frequencies of the former three bands are in very good agreement with the ν C–O of the heme a 3 -CO adduct reported by Varotsis and co-workers (1967, 1973, and 1982 cm −1 ). 29,30 However, the relative intensity among the three ν C–O bands, especially the ratio between the highest (1981–1982 cm −1 ) and lowest (1966–1967 cm −1 ) frequency bands was significantly different between our investigation and theirs. Varotsis and co-workers reported that either of these two lines could originate from the 5-coordinate species.…”
Section: Resultssupporting
confidence: 89%
“…The A-type heme in cytochrome ba 3 contains a hydrophobic hydroxyethylgeranylgeranyl group which is straight and reaches the cytoplasmic side, without interfering with the proton pathways, instead of a hydroxyethylfarnesyl chain as seen in most bacterial and eucaryotic aa 3 oxidases. Resonance Raman and time-resolved step-scan FTIR spectroscopies have been successfully applied to study the ligand dynamics and the structural and functional relationships of ba 3 and caa 3 oxidoreductases [19][20][21][22][23][24][25][26][27][28]. In this report, the reaction of oxidized Nor and ba 3 with NO will be reviewed.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of fully reduced cytochrome ba 3 , the heme a 3 -Cu B binuclear center is subjected to peculiar properties (53)(54)(55)(56)(57) characterized by a high affinity of Cu B for CO (K Ͼ 10 4 M Ϫ1 ) and a slow intramolecular ligand transfer to heme a 3 (k ϭ 8 s Ϫ1 ). As a result, cytochrome ba 3 is the only documented oxidase where the binding of CO to Cu B is exergonic and accounts for 25-30% of the total enzyme concentration (34).…”
Section: Methodsmentioning
confidence: 99%